Laparoscopic dissection of the hepatic node: The trans lesser omentum approach - Ben-Ishay, Offir (World J Gastrointest Oncol, 2020)
BACKGROUND: Diagnosis of lympho-proliferative diseases is sometimes challenging. Excisional lymph node biopsy is the standard of care. Five percent of the patients will present with abdominal or retroperitoneal lymphadenopathy alone. Advancements in endoscopic techniques allow for access to fine needle biopsy in complicated areas, but this often does not meet the standard guidelines for diagnosis. AIM: To investigate the results of laparoscopic excisional biopsy of the hepatic node (LEBHN) through a trans lesser omentum approach. METHODS: Data of all patients undergoing LEBHN were collected retrospectively from patients’ electronic charts over a period of 1 year. Data collected included age, gender, suspected disease, number of previous biopsies and biopsy method, surgical approach, intraoperative complications, operative time, post-operative complications, mortality, and final diagnosis. RESULTS: Six patients were operated in this technique during the time frame of the study, 66.6% (n = 4) were females, and median age was 55 years (range: 25-72 years). We present no conversions from laparoscopy to laparotomy, and mean operating time was 51.2 min. Mean length of hospital stay was 1 d, and morbidity and mortality were nil. Most importantly, this technique offered definite diagnosis and appropriate treatment in all patients. Final diagnosis included two patients with lymphoma (Hodgkin and Follicular), two patients with sarcoidosis, and two patients with reactive lymph nodes with no evidence of malignancy. CONCLUSION: In conclusion, this technique seems to be feasible and safe and may offer a simple approach for a definite diagnosis for what seems to be a complicated anatomical area.